Racial and Ethnic Disparities in Maternal Morbidity and Obstetric Care. Issue 6 (June 2015) - Grobman, William A.; Bailit, Jennifer L.; Rice, Madeline Murguia; Wapner, Ronald J.; Reddy, Uma M.; Varner, Michael W.; Thorp, John M.; Leveno, Kenneth J.; Caritis, Steve N.; Iams, Jay D.; Tita, Alan T.N.; Saade, George; et al.
<x xml:space="preserve">Abstract</x> OBJECTIVE: To evaluate whether racial and ethnic disparities exist in obstetric care and adverse outcomes. METHODS: We analyzed data from a cohort of women who delivered at 25 hospitals across the United States over a 3-year period. Race and ethnicity was categorized as non-Hispanic white, non-Hispanic black, Hispanic, or Asian. Associations between race and ethnicity and severe postpartum hemorrhage, peripartum infection, and severe perineal laceration at spontaneous vaginal delivery as well as between race and ethnicity and obstetric care (eg, episiotomy) relevant to the adverse outcomes were estimated by univariable analysis and multivariable logistic regression. RESULTS: Of 115, 502 studied women, 95% were classified by one of the race and ethnicity categories. Non-Hispanic white women were significantly less likely to experience severe postpartum hemorrhage (1.6% non-Hispanic white compared with 3.0% non-Hispanic black compared with 3.1% Hispanic compared with 2.2% Asian) and peripartum infection (4.1% non-Hispanic white compared with 4.9% non-Hispanic black compared with 6.4% Hispanic compared with 6.2% Asian) than others (P<.001 for both). Severe perineal laceration at spontaneous vaginal delivery was significantly more likely in Asian women (2.5% non-Hispanic white compared with 1.2% non-Hispanic black compared with 1.5% Hispanic compared with 5.5% Asian; P<.001). These disparities persisted in multivariable analysis. Many types of obstetric care examined also were significantly different according to race and ethnicity in both univariable and multivariable analysis. There were no significant interactions between race and ethnicity and hospital of delivery. CONCLUSION: Racial and ethnic disparities exist for multiple adverse obstetric outcomes and types of obstetric care and do not appear to be explained by differences in patient characteristics or by delivery hospital. LEVEL OF EVIDENCE: II